Desquamative Gingivitis in Cicatricial Pemphigoid: A Diagnostic Paradox! - Satya Ranjan Misra1, Pavitra Baskaran2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Desquamative gingivitis or gingival desquamation represents a clinical sign seen in many diseases,especially of muco-cutaneous nature. One of the common diseases, in which gingival desquamation ispresent is Mucous membrane pemphigoid (MMP) and represents a variety of chronic auto-immune subepithelialbullous diseases affecting the mucous membranes and sometimes the skin. MMP not only affectsthe oral mucosa but ocular involvement is also quite common. The severity of the disease is variable, and thegingival desquamation may be the first sign of this otherwise indolent disease and early diagnosis can reducethe morbidity especially ocular changes which could be irreversible leading to blindness can be prevented.We describe a case for documentation while describing the differential diagnosis and management of thedisease.